2014
DOI: 10.1007/s11207-014-0575-x
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Statistical Study of ICMEs and Their Sheaths During Solar Cycle 23 (1996 – 2008)

Abstract: The Appendix (Table 6) and the downloadable version available as Electronic Supplementary Material should be replaced with those given here. We regret the inconvenience.The online version of the original article can be found under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a consequence, dispersions may be important and have to be considered. In order to check if caught events correspond to real events, we have done a comparison with two lists of events, one of 279 CMEs (from July 1998 to December 2009) [see Mitsakou and Moussas , , ] and another of 443 Stream Interaction Regions (SIRs) (from July 1998 to December 2009) [see Jian et al , ]. 129 CMEs and 151 SIRs were caught by our criteria on Lnormalmnormalp*.…”
Section: A Statistical Validation Using a Superposed Epoch Analysis Based On Noaa‐poes Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, dispersions may be important and have to be considered. In order to check if caught events correspond to real events, we have done a comparison with two lists of events, one of 279 CMEs (from July 1998 to December 2009) [see Mitsakou and Moussas , , ] and another of 443 Stream Interaction Regions (SIRs) (from July 1998 to December 2009) [see Jian et al , ]. 129 CMEs and 151 SIRs were caught by our criteria on Lnormalmnormalp*.…”
Section: A Statistical Validation Using a Superposed Epoch Analysis Based On Noaa‐poes Data Setmentioning
confidence: 99%
“…The restrictive and arbitrary condition on this criterion and the geoeffectiveness of CMEs and SIRs could explain events which have not been detected by the filter. Indeed, the definition of the beginning of events can be different from a list to another (see Mitsakou and Moussas [, ] and Jian et al [] for more details). It is finally important to keep in mind that the criterion we have implemented tends to filter only the most geoeffective ones.…”
Section: A Statistical Validation Using a Superposed Epoch Analysis Based On Noaa‐poes Data Setmentioning
confidence: 99%
“…Our list is based on the merger of two lists: an ICMEs list and a magnetic clouds list. The first one was provided by Mitsakou and Moussas (2014b) and corrected a few months later (Mitsakou and Moussas, 2014a). By studying the evolution of the magnetic field, the proton density, and the temperature, the authors identified 325 ICMEs in the 1 min OMNI database in the 1996-2008 time period.…”
Section: List Of Eventsmentioning
confidence: 99%